2019
DOI: 10.1038/s41467-019-11498-x
|View full text |Cite
|
Sign up to set email alerts
|

S100A9 extends lifespan in insulin deficiency

Abstract: Tens of millions suffer from insulin deficiency (ID); a defect leading to severe metabolic imbalance and death. The only means for management of ID is insulin therapy; yet, this approach is sub-optimal and causes life-threatening hypoglycemia. Hence, ID represents a great medical and societal challenge. Here we report that S100A9, also known as Calgranulin B or Myeloid-Related Protein 14 (MRP14), is a leptin-induced circulating cue exerting beneficial anti-diabetic action. In murine models of ID, enhanced expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 51 publications
(80 reference statements)
4
27
0
Order By: Relevance
“…This study mainly analyzed the associations between serum S100A9 with the severity and the prognosis in CAP patients based on a retrospective cohort study. The present study mainly found that: Earlier studies found that S100A9 was elevated in several diseases, such as neutrophilic in ammation in asthma, insulin de ciency, atopic dermatitis and Parkinson's disease [17][18][19][20]. Moreover, a report from our laboratory indicated S100A8/S100A9 was increased in COPD patients and is positively associated with in ammatory cytokines [21].…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…This study mainly analyzed the associations between serum S100A9 with the severity and the prognosis in CAP patients based on a retrospective cohort study. The present study mainly found that: Earlier studies found that S100A9 was elevated in several diseases, such as neutrophilic in ammation in asthma, insulin de ciency, atopic dermatitis and Parkinson's disease [17][18][19][20]. Moreover, a report from our laboratory indicated S100A8/S100A9 was increased in COPD patients and is positively associated with in ammatory cytokines [21].…”
Section: Discussionsupporting
confidence: 60%
“…Released of S100A9 would activate several signaling pathways involved in the in ammatory reaction and exert important functions in a great deal of cellular processes [10,[14][15][16]. The previous studies found that S1009A9 is elevated in several diseases, such as neutrophilic in ammation in asthma, insulin de ciency, atopic dermatitis and Parkinson's disease [17][18][19][20]. Moreover, our previous study found that S100A8/S100A9 is increased in COPD patients and is positively associated with in ammatory cytokines [21].…”
Section: Introductionmentioning
confidence: 96%
“…Therefore, we focused on a functional analysis on the 13 common vitamin D supertargets of the personalized approach together with the genes AQP9, SEMA6B and THBD highlighted by the cohort approach. Based on information provided by the integrative database GeneCards and inspection of the literature [40][41][42] , the predominant cellular location of the proteins encoded by these 16 genes was determined (Fig. 4A).…”
Section: Functional Analysis Of Vitamin D Target Genes From the 13 Cmentioning
confidence: 99%
“…Released of S100A9 activates several signaling pathways and exerts important functions in a great deal of cellular processes [ 10 , 14 16 ]. The previous studies found that S1009A9 is elevated in several diseases, such as neutrophilic inflammation in asthma, insulin deficiency, atopic dermatitis and Parkinson’s disease [ 17 20 ]. In addition, our previous study found that S100A8/S100A9 is increased in COPD patients and positively associated with inflammatory cytokines [ 21 ].…”
Section: Introductionmentioning
confidence: 99%